1. Not finding help here? Sign up for a free 30min tutor trial with Chegg Tutors
    Dismiss Notice
Dismiss Notice
Join Physics Forums Today!
The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

Differentiate e^(a^2 z) with respect to z

  1. Feb 8, 2006 #1
    I am to differentiate with respect to z, where a is independent of z... (am assuming that that a is a constant?)

    a. [tex]e^{a^2 z}[/tex]=diff=>[tex]a^2 e^{a^2 z}[/tex]

    b.[tex]e^{ia z}=cos(az)+isin(az)[/tex]=diff=>[tex]-sin(az)+icos(az)[/tex]

    c. [tex](e^{-i z})^2=cos(2z)-isin(2z)[/tex]=diff=>[tex]-sin(2z)-icos(2z)[/tex]

    d. [tex]e^{-iz^2}[/tex]=diff=>[tex]-sin(z^2)-icos(z^2)[/tex]

    e. [tex]e^{az}+e^{-az}[/tex]=diff=>[tex]ae^{az}+-ae^{-az}[/tex]

    do these look alright?
  2. jcsd
  3. Feb 8, 2006 #2


    User Avatar
    Science Advisor
    Homework Helper
    Gold Member

    Whatever it is, it does not depend on z, so when z changes, a does not change. That's the definition of "constant".

    Double check b,c,d; you're forgetting the derivative of the interior (chain rule).

    note: you don't need to write e^ix in temrs of cis(x) b4 taking the derivativ; complex exponentials differentiate like regular ones, i.e.

    (e^iax)' = ia(e^iax)
    Last edited: Feb 8, 2006
  4. Feb 8, 2006 #3
    for b.

    for c.

    for d.

    how does it look?
  5. Feb 8, 2006 #4
    let me correct myself:
    for b:

    for c:

    for d:
  6. Feb 9, 2006 #5


    User Avatar
    Homework Helper

    Looks good. But as quasar987 said before, just try to differentiate it without changing to cis function.
    [tex](e ^ {iaz})' = ia e ^ {iaz}[/tex], which is a lot easier, right? This answer is exactly the same as yours:
    [tex]ia e ^ {iaz} = ia (\cos (az) + i \sin (az)) = ia \cos (az) - a \sin (az)[/tex]
Know someone interested in this topic? Share this thread via Reddit, Google+, Twitter, or Facebook

Have something to add?

Similar Discussions: Differentiate e^(a^2 z) with respect to z
  1. E^z = -2 (Replies: 12)

  2. Z^2 = z conjugate (Replies: 11)